Supplementary English reading material for the eighth-grade students - Erna Rahayu (Universitas Sarjanawiyata Tamansiswa, 2019)
The objectives of this research are to develop supplementary reading material for the eighth grade of MTs Negeri 1 Bantul and to reveal the efficacy of the developed additional materials for the eighth grade of MTs Negeri 1 Bantul. The research belongs to the educational Research and Development (R & D). The subjects of the study were the eighth-grade students of MTs Negeri 1 Bantul. The study adapted the R & D model proposed by Borg and Gall (1983). The steps of the study were conducting a needs analysis, designing a course grid, developing the materials, having expert judgment, conducting field testing, revising the elements, and writing the final product. The data were taken from document analysis, observation, and interview. The data were analyzed and described qualitatively. The result of the research showed that (1) the supplementary English reading materials developed based on the need analysis. It was used for determining the objective, indicators, and varied reading tasks and activities of the supplementary materials. The reading tasks were presented in various forms, namely true-false questions, completing sentences, multiple-choice questions, jumbled words, and jumbled sentences that developed based on Three Phase Technique steps. Each Unit consisted of three main parts: â€œTime to Start, Time to Learn, and Time to Checkâ€. The varied tasks gave the students the opportunity to improve their reading comprehension. In other words, the supplementary English reading material was useful and appropriate to be implemented for the eighth-grade students of MTs Negeri 1 Bantul. (2) The efficacy of the additional English reading materials could be described as the learning process that helped students achieve their needs, to have broad experience in learning the language, to attract the studentsâ€™ attention and involvement, and to improve studentâ€™s reading comprehension. It also provided additional learning sources for the students.